In vivo Cross-Linking MS of the Complement System MAC Assembled on Live Gram-Positive Bacteria - Khakzad, Hamed; Happonen, Lotta; Tran Van Nhieu, Guy; Malmström, Johan; Malmström, Lars (Frontiers in Genetics, 2021)
Protein-protein interactions are central in many biological processes, but they are challenging to characterize, especially in complex samples. Protein cross-linking combined with mass spectrometry and computational modeling, is gaining increased recognition as a viable tool in protein interaction studies. Here, we provide insights into the structure of the multicomponent human complement system membrane attack complex (MAC) using in vivo cross-linking mass spectrometry combined with computational macromolecular modeling. We developed an affinity procedure followed by chemical cross-linking on human blood plasma using live Streptococcus pyogenes to enrich for native MAC associated with the bacterial surface. In this highly complex sample, we identified over 100 cross-linked lysine-lysine pairs between different MAC components that enabled us to present a quaternary model of the assembled MAC in its native environment. Demonstrating the validity of our approach, this MAC model was supported by existing X-ray crystallographic and electron cryo-microscopic models. This approach allows the study of protein-protein interactions in native environment mimicking their natural milieu. Its high potential in assisting and refining data interpretation in electron cryo-tomographic experiments will be discussed.